Intertidal biodiversity and physical habitat complexity on historic masonry walls: a comparison with modern concrete infrastructure and natural rocky cliffs - Baxter, T; Coombes, M; Viles, H (Elsevier, 2023)
Maritime built heritage (e.g., historic seawalls) represents an important component of coastal infrastructure around the world. Despite this, the ecological communities supported by these structures are poorly understood. At seven locations across the UK, we compared the biodiversity and physical habitat characteristics of (1) historic (pre-1900s) masonry walls, (2) concrete walls, and (3) natural rocky cliffs. Historic masonry walls were found to support significantly more species than concrete walls, and in some locations, more diverse communities than nearby rocky cliffs. Nevertheless, community composition remained distinct between the three habitat types at each location. We also found that historic masonry walls provided substantially more cryptic space (i.e., crevices) than both concrete walls and rocky cliffs, and this is positively associated with the ecological value of these structures. Overall, our results suggest that the unique physical properties of historic masonry walls make them an important component of habitat diversity along developed coastlines.